Environment conscious consumers' opinion on selective waste management - Katalin Jäckel; Mónika Fodor; Judit Papp (Journal of Contemporary Economic and Business Issues, 2015)
Consumers have become environmentally conscious, they are keen on energy efficiency and the increasing importance of the environmental values in general has made this research relevant. We analyse the special elements of eco-marketing so that we can see which are the tools and marketing activities which might help in forming the eco-conscious attitude and behaviour. We have realised that it was not enough to inform people about different types of ecological problems globally and locally, but that they also need to be motivated to become really active. After completing the literature review we also considered the already available and relevant studies.The ecoconscious consumer behaviour was surveyed through the attitude towards selective waste collection. A standardized questionnaire based survey was carried out to analyse the consumers' selective waste collection habits as a primary research. The data was processed with SPSS. At the end of the research we made recommendations concerning the methods of marketing communication, the promotion tools and the motivation of citizens to become more eco-committed.
Keywords: Q42; Q51; Q57; 330; energy efficiency; environmental value; energy consumption; eco-marketing